C-reactive protein and N-terminal pro-brain natriuretic peptide discrepancy: a differentiation of adenoviral pharyngoconjunctival fever from Kawasaki disease - Jung Eun Choi; Hee Won Kang; Young Mi Hong; Sejung Sohn (Korean Pediatric Society, 2018)
PurposeTo differentiate adenoviral pharyngoconjunctival fever (PCF) from acute Kawasaki disease (KD) using laboratory tests before results of virus-real time polymerase chain reaction and ophthalmologic examination are obtained.MethodsBaseline patient characteristics and laboratory measurements were compared between 40 patients with adenovirus infection and 123 patients with KD.ResultsThe patients with adenovirus infection were generally older than those with KD (median: 3.9 years vs. 2 years, P=0.000). White blood cell and, platelet count, and aspartate aminotransferase, alanine aminotransferase, and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels showed significant differences between the 2 groups, but the C-reactive protein (CRP) levels did not (6.8±3.0 mg/dL vs. 8.3±5.8 mg/dL, P=0.126). In the adenovirus infection group, the CRP levels were <1, <3, <10, and ≥10 mg/dL in 2 (5%), 3 (7.5%), 30 (75%), and 5 patients (12.5%), respectively. The cutoff NT-proBNP level was 265 pg/mL. Discrepancy was defined as CRP and NT-proBNP levels of ≥3 or <3 mg/dL, and <265 or ≥265 pg/mL, respectively. Among the 35 patients with adenovirus infection whose CRP levels were ≥3 mg/dL, 29 (82.9%) showed a discrepancy. Conversely, of the 103 patients with KD whose CRP levels were ≥3 mg/dL, 83 (80.6%) showed no discrepancy. Between the groups, a significant difference in discrepancy rate was observed (P=0.000). None of the patients with adenovirus infection had CRP and NT-proBNP levels of <3 mg/dL and ≥265 pg/mL, respectively.ConclusionWith a sensitivity of 82.9% and a specificity of 80.6%, CRP and NT-proBNP levels may differentiate between adenoviral PCF and acute KD.